Language Heightens the Political Salience of Ethnic Divisions. Issue 2 (27th November 2018) - Pérez, Efrén O.; Tavits, Margit
Abstract: What makes people take ethnic divisions into account when judging politics? We consider here the possible effect of language. We hypothesize that speaking a minority tongue primes ethnic divisions, leading people to interpret politics more heavily through this prism. In two survey experiments with bilingual adults, we demonstrate that subjects assigned to interview in a minority language are indeed more likely to evaluate politics based on ethnic considerations: they rank ethnic relations as a more important political issue and they are more likely to correctly identify the anti-minority party in their political system. These results suggest that people may think about politics differently depending on the language they use.